Study and Application of Multi-Terminal Interconnection Technology to Build Smart Home Network - Jianting Han; Xiang Wan (Dianxin kexue)
Family multi-terminal interconnection is the core technology to realize smart home. Mainstream technology of family multi-terminal interconnection and networking at domestic and foreign were analyzed systematically. Through comparing technical characteristics and evaluating technical parameters of various technologies including application interconnection, IP networking and sensor networking, additionally analyzing their current situation and development trending of the industry, products suggestions and typical application of family multi-terminal interconnection and networking technology were proposed.